Heat capacity in doped graphene under magnetic fields: the role of spin splitting - Escudero, Federico Nahuel (2020)
We study the electronic heat capacity in doped graphene under magnetic fields. The partition function is calculated considering only the thermal excitations in the last occupied energy levels. Due to the large energy separation between the Landau levels (LLs) and the Zeeman splitting, at low temperatures the heat capacity is dominated by the spin excitations in the last occupied LL. Correspondingly the heat capacity oscillates with maximum amplitude at half filling of each LL. At higher temperatures the inter-LLs excitations dominate the heat capacity, with maximum amplitude at full filling factors. The oscillation amplitudes are compared with the phonon heat capacity C p. It is shown that the spin induced heat capacity oscillations have a maximum amplitude approaching 3% of C p, whereas for the inter-LLs excitations the maximum amplitude is only 0.1% of C p. These amplitudes decrease in the presence of impurities, although the effect is appreciable if the LLs broadening is bigger than the excitation energies.